Assessment of knowledge, enablers, and barriers to healthcare-seeking behaviours for urinary tract infections among pregnant women at Banadir Maternal and Child Hospital, Somalia - Kadiye, Fadumo Elmi; Wuneh, Alem Desta; Odukogbe, Akin-Tunde Ademola (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Urinary tract infections (UTIs) are common during pregnancy causing serious issue to both maternal and infantile health. However, little research has been conducted regarding what women know and do about UTIs in Somalia. Methods: A cross sectional mixed-methods approach was employed in this study to obtain both quantitative data and qualitative findings of women knowledge, experiences, and health-seeking behaviours related to UTIs. Between August and December 2024, 200 women participated in a quantitative survey, among which 21 were selected for qualitative interviews. Results: The majority (55%) of women reported having symptoms related to UTI, with the most common symptoms being fever or chills (54%), lower abdominal pain (50%), and frequent urination (42%). Only 33.5% had tested positive for UTIs in their urine. Before seeking medical attention, a large percentage of women (51%) turned to traditional remedies, such as camel milk and herbal teas. The main obstacles to accessing healthcare were transportation concerns (20.5%) and financial limitations (49.5%). Some people believed that spiritual factors caused UTIs, while others believed that poor hygiene (43%) or sexual activity (41.5%) were the main causes. The qualitative analysis revealed that people’s understanding of UTIs varied; many were aware of the symptoms but not the causes or complications. Cultural factors influenced healthcare-seeking, with women frequently avoiding medical care out of fear of judgment and stigma. Conclusions: The study underscores the need of better UTI education; the integration of biomedical and traditional practices can help in early detection and seeking healthcare at the appropriate time.